PENGOLAHAN BATOK (TAMPURUANG) KELAPA MENJADI JAM TANGAN BOTAC (BASED ON TAMPURUANG ANDALAS CREATION) - Afdhal Ahmad; Muhammad Arif Suyatman; Muhammad Surya Rahim; Faisal Majid; Rika Hariance (PROSIDING SNAST, 2018)
Coconut is one of agriculture product that is very much used by society in everyday life so that this coconut is considered as multipurpose plant. For the Minangkabau community with typical culinary features of curry and rendang, one of the main ingredients is coconut milk. This kind of cuisine is enjoyed daily by the community both in the padang food stalls and in the household. This creates a considerable amount of coconut waste, one of which is the shell (tampuruang). But the lack of utilization of waste coconut shells into high-value products, resulting in waste accumulate or burned into charcoal. Meanwhile, tampuruang actually can also be utilized economically by processing it into various innovations and creations, both in the form of souvenirs and accessories. Based on these problems we found creative ideas, creating innovations in the processing of tampuruang into a unique watch which we named BOTAC WATCH (Based On Tampuruang Andalas Creation). The creative, innovative and effective concept of BOTAC WACTH is also in line with the creative industry development program launched by the Ministry of Trade of the Republic of Indonesia. Based on the economic analysis conducted, business feasibility has a value of B / C ratio of 2.48. This indicates that the business is feasible to run, because in every Rp.1 the cost incurred will generate benefits worth Rp. 1.48. Thus this product can contribute to the growth and development of creative economy to increase the added value of products as well as enhance the competitiveness of the nation.